PENGARUH PENGEMBANGAN KARIR, PELATIHAN, PENGALAMAN MENGAJAR, DAN DISIPLIN TERHADAP MUTU PENDIDIKAN SMP MUHAMMADIYAH SUBULUSSALAM - Mawardi, Mawardi; Fauzi, Amrin; Safrida, Safrida (Jurnal Pendidikan Islam, 2018)
ABSTRACT This study aims to determine the effect of career development, training, teaching experience, and discipline on the education quality of Simpang Kiri Muhammadiyah Middle School in Subulussalam City. This study uses a quantitative method with a total sample of 30 teachers of Simpang Kiri Muhammadiyah Middle School. Data collection techniques used questionnaires, interviews, and documentation studies. The results showed that: (1) partially career development variables (X1) did not have a significant influence on the quality of education (Y) with a value of 09.1% and a significance level of 0.40 > 0.05, the hypothesis proposed by career development does not have a significant effect on the quality of education rejected. (2) Career Development (X1), Training (X2), Teaching Experience (X3) and Discipline (X3) contribute to the variable Quality of Education (Y) of 62.1% and the remaining 37.9% is influenced by other factors not included in this research variable, such as environment, leadership style, and other factors. Keywords: Career Development, training, teaching experience, discipline, Education, Muhammadiyah school.